THE RELATIONSHIP BETWEEN ACADEMIC STRESS LEVELS AND MENSTRUAL DISORDER IN CLASS IX GIRLS AT SMP NEGERI 1 COMPRENG IN 2022 - Sri Ayu Hartini; Ernauli Meliyana; Dinda Nur Fajri Hidayanti Bunga (Rena Cipta Mandiri, 2023)
Background: Menstrual disorders are a problem that many women face. (WHO) stated in 2015 that the problem of adolescents worldwide is menstrual disorders (38.45%). In Indonesia, according to 2013 Riskesdas data, the percentage of menstrual irregularities at the age of 10-29 years is 16.4%. 51% of adolescent girls cited academic stress as the cause of their menstrual cycle irregularities. Research Objectives: To determine the relationship between academic stress levels and menstrual disorders in class IX girls at SMP Negeri 1 Compreng in 2022. Research Methods: This research method is a quantitative type that is analytic with cross sectional. The population of this study was class IX students of SMP Negeri 1 Compreng using the Probability Sampling technique with the type of Simple Random Sampling. Research Results: Univariate analysis showed that most of the young women experienced severe stress 78 respondents (73.6%). Experiencing severe menstrual disorders 86 respondents (81.1%). Bivariate analysis showed that most of the young women experienced severe academic stress levels with severe menstrual disorders 71 respondents (67.0%) statistical test results using chi-square obtained p-value of 0.00 <0.05. Conclusion: There is a relationship between the level of academic stress with menstrual disorders in adolescent girls in grade IX at SMP Negeri 1 Compreng in 2022.